Construction and Validation of New Nomograms to Predict Risk and Prognostic Factors of Breast Cancer Bone Metastasis in Asian Females: A Population-Based Retrospective Study - Deng J (Dove Medical Press, 2021)
Junsen Deng,1,* Di Zhang,2,* Wenming Zhang,1 Junhui Li2 1Department of Orthopedics Surgery, Luoyang Orthopedic Hospital of Henan Province, Orthopedic Hospital of Henan Province, Zhengzhou, 45000, Henan, People’s Republic of China; 2Department of Spine Surgery, Luoyang Orthopedic Hospital of Henan Province, Orthopedic Hospital of Henan Province, Zhengzhou, 45000, Henan, People’s Republic of China*These authors contributed equally to this workCorrespondence: Junsen DengDepartment of Orthopedics Surgery, Luoyang Orthopedic Hospital of Henan Province, Orthopedic Hospital of Henan Province, Zhengzhou, 45000, Henan, People’s Republic of ChinaEmail djstougao@126.comPurpose: To construct a breast cancer bone-only metastasis (BCBM) risk and prognostic model for Asian females and provide a reference for treatment selection in breast cancer (BC) patients with bone-only metastasis (BM).Patients and Methods: The data for newly diagnosed female patients of Asian Pacific Islander (API) ethnicity between 2010 and 2018 were obtained from the Surveillance, Epidemiology, and End Results database. A total of 16,972 patients were identified. Logistic regression analyses were used to establish a risk model for BCBM. Cox proportional hazards regression analyses were used to construct nomograms for the prognosis of BC and BCBM. Subsequently, the degree of discrimination of the nomogram was evaluated using the consistency index (C-index) and receiver operating curve.Results: The main independent risk factors of BM in Asian females with BC were primary site surgery (p< 0.0001), ER (p=0.0015), and T-stage (p=0.0046). The C-index values in the training and validation cohorts were 0.933 and 0.941, respectively. The main independent risk factors of the prognosis of BC were age (p< 0.001), summary stage (p< 0.001), and grade (p=0.002). The C-index values of 5-year overall survival (OS) in the training and validation cohorts were 0.823 and 0.804, respectively. The risk factors of the prognosis of Asian females with BCBM were subtype (p< 0.001), histology (p< 0.001), and grade (p=0.033). The C-index values of 5-year OS in the training and validation cohorts were 0.793 and 0.723, respectively.Conclusion: Using population-based analysis, this study constructed a prediction model for the risk and prognosis of BM in Asian females with BC. Another newly constructed model was effective in predicting OS in BCBM patients. These models can help prevent skeletal-related events and weigh the risks and benefits of surgery for metastatic lesions in BCBM patients.Keywords: breast cancer, bone metastasis, prognosis, nomogram, SEER